A case of facial lentiginous lichen planus pigmentosus associated with Hashimoto's thyroiditis and diabetes mellitus - Fadime Kilinc; Ayse Akbas; Sertac Sener; Sibel Orhun Yavuz; Ayse Akkus; Akin Aktas (Our Dermatology Online, 2015)
Lichen planus pigmentosus (LPP) is an autoimmune, chronic and rare variant of lichen planus of unknown etiology that progresses with pigmentation. The condition is rarely observed concurrently with autoimmune diseases. In this case report, a diabetic male patient with speckled lentiginous lesions on the face, also diagnosed with concurrent autoimmune thyroiditis is presented due to the rarity of the condition and the morphological character of the lesions.